REINTERPRETATION OF ALI ASGHAR ENGINEER’S LIBERATION THEOLOGY IN THE CONTEXT OF MULTICULTURAL EDUCATION POLICY IN INDONESIA - Mahdiyin, Khizbullah Al; Rahmawati, Kiki Anita; Sahri, Iksan Kamil (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
This study reinterprets Ali Asghar Engineer’s liberation theology as a normative foundation for integrating justice, freedom, and equality into Indonesia’s multicultural religious-education policy across primary, secondary, and tertiary levels. Motivated by persistent deficits in conventional religious curricula characterized by rote learning, doctrinal literalism, and weak responsiveness to social pluralism. The research employs a qualitative literature review combining systematic database searches with content analysis and critical discourse analysis of scholarship, policy documents, and curriculum materials. Findings indicate that grounding curricula in liberationist values can reorient religious education from transmissive instruction toward emancipatory pedagogy that cultivates critical consciousness, civic agency, and intercultural competence. Implementation, however, is constrained by three interrelated barriers: structural (centralized curriculum regimes and assessment systems), cultural-ideological (conservative resistance and contestation over interpretive authority), and practical (limited teacher capacity, resources, and contextually relevant materials). The paper advances pragmatic strategies for curriculum decentralization, redesigned authentic assessment, sustained in-service teacher development, contextualized teaching modules, and deliberative engagement with religious stakeholders, coupled with pilot implementation and rigorous monitoring to ensure fidelity and scalability. By articulating a context-sensitive operationalization of the Engineer’s theology for curriculum reform, the study contributes theoretically and practically to debates on Islamic education reform and multicultural pedagogy, offering policymakers and educators an evidence-informed pathway to make religious education more just, inclusive, and transformative.